Seepage Simulation of the Proposed Makhool Dam in North Iraq - Hameed, Hasan Khalid; Abdullah, Khaled Ahmed; Irzooki, Raad Hoobi (Iraqi Journal of Science, 2023)
This study aims to simulate water seepage and identify areas of weakness in the foundations through the right and left sides of the proposed Makhool dam in northern Iraq, using the finite element method by advanced computer software (SEEP/ W, 2012). The earth fill dam is 3670 m long on the Tigris River. Many attempts were made to ascertain the program results on the supposed earth dam and compare the results with those of other analytical methods to verify the program. The results are comparable, showing that the program is suitable for use in the seepage analysis at the proposed Makhool dam. According to the seepage analysis, the quantity of seepage through the left side of Makhool is acceptable within permissible limits; however, the right side has a lot more than the left side because of the presence of cracks, fractures, and cavitations in the stratigraphic sequence of  Fatha formation at great depths in the gypsum beds under the diaphragm. The results indicate the need to lower the diaphragm about 6 m extra in the foundation's zone to a level of 49 m.a.s.l until reaching the low permeability clay bed within the foundations' zone. This action will reduce the amount of seepage and flow velocity and avoid using more grouting during the dam life. The design limits of the piezometric head (total head) were also determined, which are supposed to be read by the monitoring devices when operating the dam at the maximum level of the reservoir and the normal operating levels.